HUBUNGAN INISIASI MENYUSU DINI DENGAN IKTERUS NEONATORUM DI RSUD WATES YOGYAKARTA - Naaharani Pohlman, Mercedes; Nursanti, Ida; Very Anto, Yuni (Jurnal Media Ilmu Kesehatan, 2015)
Background: One of the recommended primary treatments for the icterus after the early initiation of breastfeeding (EIB). The EIB is when the infant starts to breastfeed immediatel after birth. The way the infant does the EIB is called the breast crawl, through which it crawls looking for breasts. Objective: The studi aims to investigate the relationship between early initiation of breastfeeding (EIB) and the icterus neonatorum at RSUD Wates, Yogyakarta. Method: This was an analytical survey method employing the cohort approach. The research population comprised mother-and- newborn-infant pairs at RSUD Wates, Yogyakarta. The sample was selected by means of the purposive sampling technique, with a sample size of 65 respondents. The research instrument was  a  standardized  observation  sheet  from  the  Ministry  of  Health.  The  analysis technique to test the hypothesis was the Chi-Square at a significance level of 95% and ? = 0.05. Results: The results of the analysis show that there is a relationship between the early initiation of breastfeeding and the icterus neonatorum at RSUD Wates, Yogyakarta with p = 0.000 and a contingency coefficient value of 0.460 or in a range of 0.40-0.599. Based on the data analysis, of 65 respondents, 38 infants (58,5%) not with the early initiation of breastfeeding, most of the respondents, namely 32 (41,5%), do not suffer from the icterus. Conclusion: There is a relationship between the early initiation of breastfeeding and the icterus neonatorum at RSUD Wates, Yogyakarta. Health officials should continuously provide information about the importance of and suggest the application of the early initiation of breastfeeding for newborn infants. Mothers should improve their awareness of doing the early initiation of breastfeeding and provide good breast milk. Keywords: Early initiation of breastfeeding, icterus neonatorum